Online Learning Communication Model During the Covid-19 Pandemic at Palu City Vocational High School - Jamaluddin M Arif; Muhammad Khairil; Ilyas Lampe (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims: 1) To understand and analyze the conceptualization of online learning at Vocational High Schools in Palu City, 2) To understand and analyze the communication model in online learning at Vocational High Schools in Palu City, and 3) To understand and analyze what patterns of online learning are expected by students of the Palu City Vocational High School. This research is qualitative research using a case study approach. The unit of analysis in this study is SMK Negeri 2 Palu and SMK Negeri 5 Palu. The informants of this study were school principals, committee members, parents/guardians, teachers and students. Data collection was carried out through observation, in-depth interviews and documentation. The research results show that first, the conceptualization of online learning refers to the circular letter of the Ministry of Education and Culture No. 4 of 2020 regarding the implementation of education policies during the emergency period of the spread of Coronavirus Disease (Covid-19), that the learning process is carried out online. Second, the communication model in online learning is predominantly one-way, with a scheme for government regulations regarding technical online learning in Vocational High Schools (SMK) carried out by teachers and students using online applications, namely via whatsapp, cloud-x, zoom, google classroom, google meets with the aim of students remaining active in learning and receiving learning materials even in a pandemic situation. Third, the online learning pattern expected by students is varied, fun, exhilarating and interesting.